Long-term outcome after successful lower extremity free flap salvage - Bigdeli, Amir Khosrow; Gazyakan, Emre; Schmidt, Volker-Jürgen; Bauer, Christoph; Germann, Günter; Radu, Christian Andreas; Kneser, Ulrich; Hirche, Christoph (Journal of reconstructive microsurgery, 2019)
Background Vascular occlusion after free flap surgery has become a rare complication but still poses a major challenge. It necessitates urgent re-exploration, but the logistic challenge to provide sufficient resources for the emergency intervention remains. The aim of this study was to analyze the long-term outcome after successful lower extremity free flap salvage. Methods A single-center retrospective study including long-term follow-up was approved by the local ethics committee. From January 1999 to December 2010, a total of 581 free flaps were performed for lower extremity reconstruction. Eighty-six flaps required emergency re-exploration, of which 65 could be salvaged. Fifteen salvaged flaps were excluded from the study because of secondary amputation. Of 50 patients, 29 (6 females and 23 males) were eligible for follow-up. The mean follow-up time was 54.5 ± 32.9 months. Health-related quality of life (Short Form 36 [SF-36]) and scar quality (Vancouver Scar Scale [VSS]) were analyzed. Results The overall flap survival rate was 94.7% and the total loss rate was 5.3%. The re-exploration rate was 14.8% (86 of 581 flaps). The salvage rate was 75.6% (65 of 86 flaps). Twenty-one free flaps were totally lost (24.4%). Partial flap loss occurred in 12 cases (14.0%); 67.5% of the vascular complications occurred during the first 24 hours, 20.9% between 24 and 72 hours, and 11.6% after more than 72 hours. The mean time from the first signs of impaired flap perfusion to re-exploration was 1.3 ± 0.4 hours, and from free tissue transfer to re-exploration was 16.2 ± 1.9 hours. The overall scar appearance was good with an average VSS score of 4.0 points. The average SF-36 physical component score was 54.4 ± 5.4 and the mental component score was 63.1 ± 10.7. Conclusion Careful monitoring and the opportunity for urgent re-exploration are the key to success for free flaps salvage. Following these principles, an acceptable long-term outcome can be achieved.
Published online: October 16, 2018
Gesehen am 15.07.2019